2012
DOI: 10.1016/j.febslet.2012.10.053
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐101 suppresses SOX9‐dependent tumorigenicity and promotes favorable prognosis of human hepatocellular carcinoma

Abstract: a b s t r a c tWe previously showed that high expression levels of SOX9 correlate with hepatocellular carcinoma (HCC) progression. However, the exact role that SOX9 plays in HCC remains unclear. In this study, we firstly confirmed that miRNA-101 directly targets SOX9 in HCC. Ectopic expression of miR-101 significantly inhibited HCC cell proliferation and tumorigenicity by targeting SOX9. Moreover, the down-regulation of miR-101 in clinical HCC tissues correlates with tumor aggressiveness and poor prognosis. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(89 citation statements)
references
References 32 publications
3
86
0
Order By: Relevance
“…Wang et al (2016) illustrated SOX9 was associated with cell proliferation, migration and invasion and SOX9 was an important functional mediator of miR-124 in lung adenocarcinoma cells. Zhang et al (2012) found miR-101 suppressed SOX9-dependent tumorigenesis in human hepatocellular carcinoma. Together, these findings suggest that SOX9 may be a molecular marker that is involved in tumorigenesis.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Wang et al (2016) illustrated SOX9 was associated with cell proliferation, migration and invasion and SOX9 was an important functional mediator of miR-124 in lung adenocarcinoma cells. Zhang et al (2012) found miR-101 suppressed SOX9-dependent tumorigenesis in human hepatocellular carcinoma. Together, these findings suggest that SOX9 may be a molecular marker that is involved in tumorigenesis.…”
Section: Discussionmentioning
confidence: 96%
“…The effect of SOX9 on the proliferation of osteosarcoma cell lines was evaluated by the MTT (Sigma, USA) methods according to the protocols of the previous study (Zhang et al 2012). Cells were seeded in 96-well plates.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Of all the different expression microRNA, the significant downregulation of miR-101 in cervical cancers of Uygur women is consistent with the reported decrease of miR-101 in prostate cancer (Pang et al, 2010;), colon (Chandramouli et al, 2012Strillacci et al, 2013), liver cancer (Zhang et al, 2012), non small cell lung cancer (Zhang et al, 2011), breast cancer (Wang et al, 2012), and gastric cancer (Wang et al, 2010). Our data showed that miR-101 expression was significantly reduced in cervical cancer, which may play a critical role in the occurrence and development of cervical cancer.…”
Section: Discussionsupporting
confidence: 81%
“…It has been reported that dysregulation of miR-101 is associated with tumorigenesis, development and invasion, which is essential in multiple cancer types, including bladder cancer (24) and human hepatocellular carcinoma (25,26). Furthermore, it has bee reported that overexpression of miR-101 induced apoptosis in gastric cancer cells (27).…”
Section: Discussionmentioning
confidence: 99%